Qualitative Study of the Incidence of Autism among Students at State Special School (SLB) 1 Parepare City - Rahmi Amir; Risdayanti Risdayanti; Nurlinda Nurlinda; Rasidah Rasidah; Abd Farid Lewa (Poltekkes Kemenkes Palu, 2023)
This research explores the risk factors for the occurrence of autism among students at Special Needs School (Sekolah Luar Biasa or SLB) Negeri 1 in the city of Parepare. Autism is a developmental disorder that affects a child's social interaction, communication, and behavior. The exact cause of autism is still unknown, but several factors such as genetics, environment, and prenatal factors have been identified as possible causes. This study used a qualitative method, conducting in-depth interviews with parents of autistic students, therapy counselors, and teachers of autistic students. Results of the research indicate that traditional factors such as a history of medication during pregnancy, viral infections, and the birth weight of the baby do not have a significant association with autism among students at SLB Negeri 1 Parepare. However, other factors such as imbalances in the nervous system, exposure to chemicals, and exclusive breastfeeding for less than six months may contribute to the occurrence of autism.This research emphasizes the need for a deeper understanding of the risk factors for autism that may vary in different populations. Recommendations include avoiding the consumption of non-prescribed medications during pregnancy, reducing exposure to harmful chemicals, and promoting exclusive breastfeeding for a minimum of six months. The government also needs to raise awareness about autism and provide appropriate facilities for children with this disorder. This research contributes to a better understanding of the risk factors for autism at SLB Negeri 1 Parepare.